An Analysis of Intrinsic and Extrinsic Elements in James Cameron’s Film Titanic - Semiun, Thresia Trivict (Universitas Nurul Jadid, 2025)
This study aimed to analyze the intrinsic and extrinsic elements of the film Titanic, directed and written by James Cameron. Using a descriptive qualitative method, the researcher served as the primary instrument for data collection and analysis. Data were gathered through repeated viewing of the film and selecting relevant dialogue to identify intrinsic and extrinsic structures. The intrinsic elements examined include theme, plot, characterization, setting, and point of view. The extrinsic elements analyzed consisted of social, educational, religious, and cultural values. The findings showed that Titanic reflected a love story between individuals from different social backgrounds, depicted through a flashback narrative, complex character development, and rich settings. The extrinsic aspects highlighted values such as cooperation, responsibility, sacrifice, and cultural appreciation. This analysis was expected to contribute to a deeper understanding of literary and cinematic elements, particularly for students studying literature through film.